2018
DOI: 10.23996/fjhw.74405
|View full text |Cite
|
Sign up to set email alerts
|

Living Lab services promoting health in the community through participation

Abstract: In the time of urban growth, people should be at the heart of development, too often they are forgotten. However, growth poses also a great possibility. Cities can transform into open innovation Living Labs, places to experiment and co-create with creative ideas to improve people’s health and wellbeing. Open innovation Living Lab is one-step for city towards smart and healthy society. This requires bold political choices, strategic level approach, open-minded governance and new operational models. The Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In light of the above context, the present study empirically set up and operated a living lab to put the model into practice and explore pathways for behavioural change and sustainable problem-solving in the context of industry-government-academia-private collaboration and innovation: the so-called Quadruple Helix Open Innovation model [47,48]. More specifically, the present study employed a demonstration field in Tokyo, Japan and collaborated with the city residents in a dedicated living lab.…”
Section: Aim and Objectivesmentioning
confidence: 99%
“…In light of the above context, the present study empirically set up and operated a living lab to put the model into practice and explore pathways for behavioural change and sustainable problem-solving in the context of industry-government-academia-private collaboration and innovation: the so-called Quadruple Helix Open Innovation model [47,48]. More specifically, the present study employed a demonstration field in Tokyo, Japan and collaborated with the city residents in a dedicated living lab.…”
Section: Aim and Objectivesmentioning
confidence: 99%
“…For example, Nymberg et al (2019) found that older patients in primary care expressed ambivalent feelings towards new technologies and needed tailor-made solutions for user acceptance. Collaboration and involvement of all stakeholders (including users) allows all voices to be heard in the innovation process, resulting in better products and services that are accepted by users and fit the context of use (Holopainen et al , 2018). This is especially relevant for healthcare, with its complexity, various types of users and stakeholders, conflicting interests and wide range of possible solutions to innovation problems (Almirall et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Participatory development processes and principles of co-creation have been promoted in the recent development of eHealth solutions [4,5]. For being effective and responsive, matching innovative ideas with customer needs is considered a necessity for value co-creation [5,6].…”
Section: Introductionmentioning
confidence: 99%